Nanotechnology and herbal products: Advances and perspectives in the treatment of diabetes and some of its complications - Jors Vargas, Laura García, Yolima Baena (Journal of Applied Pharmaceutical Science, 2023)
Diabetes is one of the diseases with the highest prevalence and mortality around the world. Nanotechnological applications for herbal medicines are a promissory approach to overcoming some issues related to the technological adequation of substances to treat this disorder. Despite this being a current topic due to the rising number of publications in the last few years, some composition, pharmaceutical, and effectiveness characteristics have not been analyzed. From a review of articles, selected based on specific criteria and their subsequent analysis, it was possible to describe the most studied nanosystems applied to natural products, with prospective application in diabetes, finding that systems that employ substances with polyphenolic compounds and, nanoparticles and nanofibers that include polymers and lipids as materials, represent the largest number of studies to date. The influence of obtention techniques over some pharmaceutical properties like stability and their effectiveness were also analyzed, finding that these systems could enhance some characteristics and positively impact diabetes treatment.
Keywords: Diabetes, nanotechnology, herbal extracts, polymeric nanoparticles, solid lipid nanoparticles, nanofibers